A 5-HT1Areceptor promoter polymorphism influences fronto-limbic functional connectivity and depression severity in bipolar disorder. (30th December 2017) - Vai, Benedetta; Riberto, Martina; Ghiglino, Davide; Poletti, Sara; Bollettini, Irene; Lorenzi, Cristina; Colombo, Cristina; Benedetti, Francesco
Highlights: GG patients present an higher Amy–VLPFC connectivity compared to C carriers. rs6295 moderates the relationship between Amy–VLPFC coupling and clinical outcome. Corticolimbic connectivity predicts higher depressive symptomatology in GG patients. Genetic variations in serotonergic system could affect outcome in bipolar disorder.